Pengaruh Pertumbuhan Ekonomi dan Pengangguran terhadap Kemiskinan di Provinsi Jambi - Beid Fitrianova Andriani; Arsa Arsa; Ferlinda Agustina (Lembaga Yasin AlSys, 2026)
Poverty remains one of the major challenges faced by developing countries, including Indonesia, and its level in Jambi Province has tended to fluctuate in line with changes in regional economic conditions. In this context, economic growth and unemployment are viewed as two factors that may influence poverty. This study aimed to analyze the effects of economic growth and unemployment on poverty in Jambi Province. The study employed a quantitative approach using secondary data obtained from Badan Pusat Statistik (BPS). The analyzed data comprised a combination of time-series and cross-sectional data for the 2018–2024 period. The analytical method used was panel data regression with the Random Effect Model (REM) approach. The results showed that, partially, economic growth had a significant effect on poverty in Jambi Province, whereas unemployment had no significant effect. However, simultaneously, economic growth and unemployment jointly had a significant effect on poverty in Jambi Province. These findings indicate that poverty dynamics in Jambi Province are more closely associated with changes in economic growth, although both variables still exert a joint influence. Therefore, this study underscores the importance of formulating integrated economic policies to support poverty reduction efforts in Jambi Province.